1993
DOI: 10.1016/0735-1097(93)90049-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the hemodynamic significance of coronary artery stenosis: Analysis of translesional pressure-flow velocity relations in patients

Abstract: These data demonstrate that in branching human coronary arteries, a close relation exists between translesional hemodynamics and distal coronary flow velocity. Translesional coronary flow velocity is a new and easily applicable method for determining the hemodynamic significance of coronary artery stenoses that is superior to angiography and can be applied at the time of diagnostic catheterization. These data will provide a rational approach to making decisions on the use of coronary interventional techniques … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(52 citation statements)
references
References 34 publications
1
51
0
Order By: Relevance
“…Coronary flow-derived parameters include the diastolic to systolic velocity ratio and proximal to distal velocity ratio. 23 Both parameters were, however, shown to have limited diagnostic accuracy for myocardial ischemia when compared with CFVR. 24 Pressurederived parameters that have been investigated previously include the transstenotic pressure gradient during baseline conditions, 25 resting distal pressure to aortic pressure ratio, 26 Data are presented as mean±SD or median (interquartile range).…”
Section: Evaluation Of Functional Lesion Severity Without Hyperemiamentioning
confidence: 99%
“…Coronary flow-derived parameters include the diastolic to systolic velocity ratio and proximal to distal velocity ratio. 23 Both parameters were, however, shown to have limited diagnostic accuracy for myocardial ischemia when compared with CFVR. 24 Pressurederived parameters that have been investigated previously include the transstenotic pressure gradient during baseline conditions, 25 resting distal pressure to aortic pressure ratio, 26 Data are presented as mean±SD or median (interquartile range).…”
Section: Evaluation Of Functional Lesion Severity Without Hyperemiamentioning
confidence: 99%
“…In the previous studies, Donohue et al [40] concluded that within branching coronary circulations, translesional flow velocity ratios < 1.7 are associated with translesional pressure gradients < 30 mmHg.…”
Section: Translesional Hemodynamic Variablesmentioning
confidence: 97%
“…However, because of the complexity in the interpretation of CVR, pressurederived FFR is the preferred measurement for lesion assessment and outcome of PCI. Coronary physiologic measurements associated with major clinical outcomes are supported by numerous studies (Table 23) (632,637).…”
Section: Coronary Artery Pressure Andmentioning
confidence: 98%
“…IVUS increasingly is also being used to measure the volume of intimal hyperplasia in experimen- On the other hand, CVR is the ratio of hyperemic to basal flow and reflects flow resistance through the epicardial artery and the microvascular bed. CVR less than 2.0 is positively correlated to abnormal stress perfusion imaging (632)(633)(634). In some cases, the uncertainty as to whether the impaired flow reserve is due to the target stenosis or to an abnormal microcirculation may be reduced by use of relative coronary flow reserve (rCVR, which is equal to CVR of the target vessel divided by CVR of the reference vessel).…”
Section: Coronary Artery Pressure Andmentioning
confidence: 99%